(untitled) (Mongolian Journal of Agricultural Sciences, 2014)
The aim of this study is to determine the morphological characteristics of cones and pollens of Pinus sylvestris L (Scots pine). The average length of the pollen was measured 9.3 μm, and the width was 11.4 μm. Comparing to results of previous studies conducted by Jamyansuren S. and Suntsov A. B during the period of 1983 to 1985, the current morphological measurements of cones have decreased by 5 mm and number of cone scales reduced by 12.6. DOI: http://dx.doi.org/10.5564/mjas.v11i2.226 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.92-95